Age-Related Changes In The Oxidative Status And Antioxidant Capacity In Different Brain Regions Of Spontaneously Hypertensive Rat [QD63.X6 T258 2005 f rb]. - Tee, Chee Woui (2005)
Oxidant/antioxidant imbalance has been implicated in the pathogenesis of neurological disorders associated both with aging and hypertension.